The Use Of Banana Stem In The Making Of Dendeng Batokok - Lu’luwatin Rosdiana Aprilia; Sara Rabasari; Mentari Sonya S (Gastronomy Tourism Journal, 2022)
Dendeng batokok is a processed culinary delicacy from West Sumatra or the Minang tribe that is made from beef or buffalo meat. The authors of this investigation substituted banana stems for beef. This study employs experimental research methodologies, with data gathered through observation, panelist evaluation, and a review of the literature. Meanwhile, the Organoleptic Test and Preference Test are being used for data analysis. The results showed that beef dendeng made from banana stems tasted similar to beef dendeng with higher nutritional value (calories, fat, and carbs) than beef dendeng with lower production costs.